PENGARUH PEMBERDAYAAN DAN DUKUNGAN SOSIAL TERHADAP KINERJA PEGAWAI DINAS PEKERJAAN UMUM PENATAAN RUANG DAN PERUMAHAN RAKYAT PROVINSI KALIMANTAN TIMUR - Hidayah, Naniek Naniek ] (EKONOMIA, 2019)
The Influence of Empowerment and Social Support on the Performance of Employees of the Public Works Agency for Spatial Planning and Public Housing of East Kalimantan Province